(untitled) (Hakim: Jurnal Ilmu Hukum dan Sosial, 2026)
This study is motivated by the odd mismatch between legal norms and what actually happens in day-to-day practice, when it comes to ensuring access to justice for people with mental disabilities who are victims of sexual violence. Legally speaking, protection is more or less guaranteed, but, in reality, implementation just keeps running into structural and institutional obstacles, which makes it feel like everything sort of falls apart in practice. Overall, this research wants to look closely at the kinds of discrepancy between norms and practice, and then to pin down what barriers really affect access to justice. The method uses a qualitative socio-legal approach, sorta combining normative review with empirical inquiry. Data were gathered via document analysis and also through in-depth interviews with informants who were selected purposively. After that, the material was analyzed thematically, even if the process felt a bit slower than planned. The findings suggest that barriers show up at nearly every stage of the judicial process. Structural barriers appear as the main cause, and they are followed by procedural constraints, cultural pressures, plus even some normative inconsistencies that shouldn’t really be there. In addition, non-adaptive procedures, limited support, stigma directed toward victims, and weak coordination between agencies all help widen the gap between what the law says and what victims experience. The contribution here is mostly the integrative approach that blends normative and empirical analysis within a sociology of law perspective, with a particular attention to mental disability. The broader implication is pretty clear: there is a need for judicial system reform that is more inclusive, more adaptive, and more responsive, so that substantive access to justice can become something concrete rather than just a promise on paper.